2022
DOI: 10.3390/antibiotics11111480
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Ceftriaxone in Neisseria gonorrhoeae: Rapid Induction in WHO P Reference Strain and Detection in Clinical Isolates

Abstract: In addition to antimicrobial resistance, bacteria contain other mechanisms to survive antibiotic exposure such as tolerance, defined as the ability to slow metabolism by the extension of the lag phase without altering antimicrobial susceptibility. In a number of bacterial species, tolerance has been associated with treatment failure and infection chronicity and is found to precede and facilitate antimicrobial resistance. It is unknown if tolerance can be induced in Neisseria gonorrhoeae. In this study, we dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Previously, we reported that tolerance to CRO can be induced in CRO-susceptible (<0.004 µg/mL) N. gonorrhoeae WHO P reference isolate [ 17 ]. In the current analysis, we describe, for the first time, the mutations associated with emergence of CRO tolerance in N. gonorrhoeae.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we reported that tolerance to CRO can be induced in CRO-susceptible (<0.004 µg/mL) N. gonorrhoeae WHO P reference isolate [ 17 ]. In the current analysis, we describe, for the first time, the mutations associated with emergence of CRO tolerance in N. gonorrhoeae.…”
Section: Discussionmentioning
confidence: 99%
“…We recently induced tolerance to ceftriaxone (CRO) in N. gonorrhoeae reference isolates (WHO P) [ 17 ]. A highly susceptible CRO reference strain, WHO P with a CRO MIC of 0.004 µg/mL, was used [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 In addition, tolerance to ceftriaxone was found in clinical samples. 12 However, if the surveillance data cannot interpret the current situation of gonorrhea epidemic, misleading may be inevitable in policy making for gonorrhea prevention and control. Many factors may affect the integrity and accuracy of surveillance data.…”
Section: Introductionmentioning
confidence: 99%